Housing justice as expansion of people’s capabilities for housing - Boram Kimhur (A+BE: Architecture and the Built Environment)
Housing inequality is a growing concern in our society. In recent decades, this inequality has been exacerbated by the phenomenon of housing being financialized and commodified as a means for wealth accumulation. Management of financial institutions and housing markets has become the centre of attention in policy discussion. The questions of how to promote the moral values tied to housing, such as human rights, dignity and freedom, and how to better enable people to access suitable housing have been marginalized. As a way forward, the states’ re-intervention and redistribution policies, and the human rights-based approach to housing policies are discussed, but this thesis advocates for a more ambitious paradigm shift. By extending Amartya Sen’s capability approach to housing, the thesis argues for resetting the primary goal of housing policies as expansion of people’s capabilities for housing—expanding opportunity, ability and security to lead their valued ways of residing—beyond the distribution of monetary and material resources for housing, such as housing benefits and dwelling units. This thesis presents the theoretical foundations of this argument and proposes basic principles to guide housing policies, which can serve as a normative basis of housing debates on necessary policy actions. An essential tool to guide housing policies towards this newly proposed goal is to evaluate policy outcomes and housing affairs of people—well-being, deprivation and inequality in housing—with capability considerations. The thesis suggests how this evaluation can be done and can help policies address the inequalities in what people can do to pursue their suitable housing options and how well they are actually residing.